2009
DOI: 10.1158/0008-5472.sabcs-6120
|View full text |Cite
|
Sign up to set email alerts
|

Oral combination chemotherapy with capecitabine and cyclophosphamide in patients with metastatic breast cancer: phase II study.

Abstract: #6120 Background : Capecitabine and cyclophosphamide(XC) are shown to have a synergistic effect in the preclinical study and can be given orally with non-overlapping toxicities. Phase I study of XC was conducted for metastatic breast cancer patients and the recommended dose was 1657/mg/m2/day of X and 65mg/m2/day of C, respectively, which were to be given daily for 2 weeks at every 3-week schedule. We conducted phase II study with this regimen.
 Patients and methods: Women with advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 0 publications
4
9
0
Order By: Relevance
“…In the SELECT BC trial, the median time to failure (TTF) was 8.0 months in the group administered S-1 as the rst-line chemotherapy (4). Regarding capecitabine+CPA combination treatment, two phase II studies have already reported this regimen's e cacy (15,16). The ORRs of 35.6% and 30.3% in those studies are consistent with our present study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the SELECT BC trial, the median time to failure (TTF) was 8.0 months in the group administered S-1 as the rst-line chemotherapy (4). Regarding capecitabine+CPA combination treatment, two phase II studies have already reported this regimen's e cacy (15,16). The ORRs of 35.6% and 30.3% in those studies are consistent with our present study.…”
Section: Discussionsupporting
confidence: 90%
“…The ORRs of 35.6% and 30.3% in those studies are consistent with our present study. The median PFS in those studies were 6.6 months and 5.2 months, respectively (15,16).…”
Section: Discussionmentioning
confidence: 96%
“…In the SELECT BC trial, the median time to failure (TTF) was 8.0 months in the group administered S-1 as the first-line chemotherapy (4). Regarding capecitabine+CPA combination treatment, two phase II studies have already reported this regimen's efficacy (15,16). The ORRs of 35.6% and 30.3% in those studies are consistent with our present phase II study's values.…”
Section: Discussionsupporting
confidence: 89%
“…The ORRs of 35.6% and 30.3% in those studies are consistent with our present phase II study's values. Those studies' median PFS values were 6.6 months and 5.2 months, respectively (15,16). All-grade leukopenia was observed in 19.4% of our present series, and one patient was unable to continue the therapy.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation